The tuning of a small four-stroke spark ignition engine for flexible valve timings through numerical approach - Mohd Razali, Hanipah; M. Haziq Adham, Rosli; M., Kettner (EDP Sciences, 2019)
Variable valve timing has been implemented by various manufacturers to improve internal combustion engine performance while operating at wide speed and load ranges. A novel flexible valve timing system for a small four-stroke engine is currently under development by Automotive Engineering Research Group (AERG) in Universiti Malaysia Pahang (UMP). In this paper, a compherenhensive intake and exhaust tuning for th flexible variable valve timing is presented. A numerical assessment has been conducted to the engine in a one dimensional engine simulation using validated simulation model. There are eight valve timing configurations investigated for the tuning for three speed regions. The simulation shows a positive and significant impact to the engine performance in three approaches; namely late intake valve closing, early intake valve closing and late exhaust valve closing. These approaches sufficiently covered the whole range of engine speeds.